Penggunaan Bahan Ajar Digital Berbasis Inquiry pada Masa Pandemi Covid-19 untuk Mata Kuliah Pembelajaran IPA di SD Kelas Tinggi - Niki Dian Permana P; Imelda Free Unita Manurung (el-Ibtidaiy:Journal of Primary Education, 2020)
This study aims to determine the benefits of using inquiry-based digital teaching materials during the Covid-19 pandemic for natural science learning subjects in high-grade elementary schools. The method used in this research is descriptive method with the aim of obtaining a description of the usefulness of digital teaching materials in online learning for elementary school teacher education (PGSD) students. Digital teaching materials are one of the solutions that can be given to problems that occur during the pandemic. COVID-19 so that students' needs for teaching materials are still fulfilled even though the learning that is taking place is not carried out face-to-face in class. This teaching material is structured with self-instructional, adaptive, self-contained, and user friendly characteristics. The data analysis in this study is based on four indicators, namely the ability of students to use digital teaching materials, student activeness in learning using digital teaching materials, the effectiveness of learning using digital teaching materials and student responses to learning using digital teaching materials. The instrument used in collecting data in this study was a questionnaire. Based on the results of data analysis, it was found that 75% of students were able to use applications as science teaching materials, 65% of students seemed to be active in learning, 85% of students stated that digital teaching materials were very effective in online learning, and 90% of student responses to learning were positive.